Building the Islamic Generation: Islamic Education Learning Methods for the Alpha Generation ast Karya Bhakti Private Junior High School - Rejeki, Tiara; Sari, Vika Permata; Manik, Wahyuni (Al'Adzkiya Journal, 2025)
Islamic Religious Education (PAI) has a very important role in shaping the character of the Alpha generation, which is now growing in the digital era. Amidst the rapid advancement of technology, this generation is faced with challenges in understanding and internalizing Islamic values. Unfortunately, traditional learning methods are often less effective in dealing with these dynamics. Therefore, innovative approaches are needed, such as project-based learning, gamification, and the use of interactive digital media. This journal also emphasizes the importance of collaboration between schools, families, and communities as the key to supporting student character development. Through the right approach, Islamic Religious Education has the potential to help the Alpha generation become individuals who are not only emotionally intelligent, but also have moral integrity, and are able to internalize Islamic values in everyday life.